Effect of addition of vitamin C in diluent medium for quality of dairy cow (Bos taurus) spermataozoa after thawing - Fifi Afiati; D.A. Lestari; D.M. Malini (Indonesian Center for Animal Research and Development (ICARD), 2016)
The process of freezing and thawing of semen could lead spermatozoa death and low fertility for alive spermatozoa. This research was subjected to determine the optimum concentration of vitamin C in diluent media to improve the quality of non-sexing and sexing result of thawed dairy cattle (Bos taurus) spermatozoa. The method used was completely randomized design with 3x4 factorial consisting of spermatozoa isolation and vitamin C concentration. Spermatozoa isolation factors were non-sexing and sexing results (X and Y spermatozoa). Vitamin C concentrations factors were 0% (K); 0.25% (P1); 0.50% (P2) and 0.75% (P3). Data were analyzed using analysis of variance (ANOVA) and Duncan's Multiple Range Test 95%. The optimum concentration of vitamin C in diluent media to improve the quality of non-sexing thawed dairy cattle (Bos taurus) spermatozoa was 0.25%. While the optimum concentration of vitamin C in diluent medium to improve quality of thawed dairy cattle (Bos taurus) spermatozoa both X and Y was 0.50%. Administration of vitamin C in diluent media could improve the quality of thawed non-sexed and sexed (X and Y spermatozoa) spermatozoa in dairy cattle (Bos taurus).Kata Kunci: Spermatozoa, Bos taurus, Vitamin C, Sexing, Diluent, Thawing